(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
Shwitra is kind of skin disease which has serious cosmetic issue. It is skin disease with unknown etiology in which skin loses its color and develops white patches. Shwitra occurs when pigment producing cells in the skin stop functioning. It is considered as autoimmune disorder in which melanocytes gets destroyed and dies. Shwitra is Tridoshaj according to Ayurveda. Various Hetus which causes Shwitra leads to aggravation of Pitta dosha, which in turn vitiates the other Doshas. Ayurveda quotes Shwitra as Deergha rogha. According to Ayurveda, Shwitra comes under Kushta category. Shwitra is Kashtasadhya vyadhi, may not be cured completely or, it takes long time to cure. First Shodhan chikitsa is done followed by Shaman chikitsa. Hetus like Chardi nigrahana, Papkarma, Atisevan of Katu, Amla, Lavan rasa, Atimatra bhojan. Various drugs are mentioned in Bhavprakash Nighantu for Shaman chikitsa. These drugs are easily available, economical and highly efficacious. Drugs mentioned in Bhavprakash are Bhallatak, Ashwagandha, Khadir, Shinshapa, Kakanasa, Bakul, Kakudumbar, Bijak, Tinish Dravyas which are mentioned above in Bhavprakash Nighantu should be acting through its Rasa virya vipak and Prabhav. Drugs perform Sphotajanan activity, production of melanocytes and Rakta prasadan.